2019
DOI: 10.1002/mrc.4842
|View full text |Cite
|
Sign up to set email alerts
|

Water and oil signal assignment in low‐moisture mozzarella as determined by time‐domain NMR T2 relaxometry

Abstract: A time‐domain 1H nuclear magnetic resonance relaxometry method was elaborated for the rapid microstructural characterization of mozzarella cheese. For this purpose, there is a strong need to know how the experimentally determined T2 relaxation time distribution can be related to specific constituents in mozzarella. In this study, a detailed investigation is offered for fresh and aged low‐moisture mozzarella cheese, often applied as a pizza cheese, by application of both a conventional Carr–Purcell–Meiboom–Gill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These results were in agreement with those of Kuo and Gunasekaran (2009) and McMahon et al (1999) who investigated the microstructure of LMPS Mozzarella cheeses during 14 or 21 d storage at 4°C using scanning electron microscopy, and described how the uptake of moisture resulted in swelling of the calciumphosphate para-casein matrix, and the formation of a reticular network of distinctly defined flat globules occluded by the para-casein matrix. Similarly, Gianferri et al (2007) reported substantial displacement of 'serum water', described as the accumulated water in protein fiber channels, to 'junction zone water', described as the water that could be seen as an integral part of the protein structure, in retail Mozzarella di Bufala Campana cheese (moisture content of 55 to 60%, wt/wt) during storage at 8°C for 7 d. Previous studies (Smith et al, 2017;Vermeir et al, 2019) evaluated storage-related changes in industrial LMPS Mozzarella using 1 H-NMR relaxometry, but did not relate these changes to the concurrent changes in other physicochemical or functional characteristics. The objectives of the current study were firstly to establish the relationships between the biochemical, water-distribution, and functional characteristics in industrial LMPS Mozzarella cheeses during storage at 4°, and secondly to monitor inter-vat variability in these characteristics between the cheeses sampled on 7 different production dates over a 1.5 year period.…”
Section: Introductionmentioning
confidence: 88%
“…These results were in agreement with those of Kuo and Gunasekaran (2009) and McMahon et al (1999) who investigated the microstructure of LMPS Mozzarella cheeses during 14 or 21 d storage at 4°C using scanning electron microscopy, and described how the uptake of moisture resulted in swelling of the calciumphosphate para-casein matrix, and the formation of a reticular network of distinctly defined flat globules occluded by the para-casein matrix. Similarly, Gianferri et al (2007) reported substantial displacement of 'serum water', described as the accumulated water in protein fiber channels, to 'junction zone water', described as the water that could be seen as an integral part of the protein structure, in retail Mozzarella di Bufala Campana cheese (moisture content of 55 to 60%, wt/wt) during storage at 8°C for 7 d. Previous studies (Smith et al, 2017;Vermeir et al, 2019) evaluated storage-related changes in industrial LMPS Mozzarella using 1 H-NMR relaxometry, but did not relate these changes to the concurrent changes in other physicochemical or functional characteristics. The objectives of the current study were firstly to establish the relationships between the biochemical, water-distribution, and functional characteristics in industrial LMPS Mozzarella cheeses during storage at 4°, and secondly to monitor inter-vat variability in these characteristics between the cheeses sampled on 7 different production dates over a 1.5 year period.…”
Section: Introductionmentioning
confidence: 88%
“…We first examined the relaxation behaviors of the six vegetable oil samples by applying the inversion recovery sequence and the above-defined CPMG sequence to obtain the T 1 and T 2 relaxation times of the samples, respectively [ 33 , 34 ]. The other experimental parameters applied were 4 scans, 90° pulse width of 2.72 μs, 180° pulse width of 5.12 μs, 50 ms acquisition time, and a 2 s recycle delay time to allow all the protons to return to thermal equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…Another population with relaxation time (T2 2 ) ranging between 33 and 39 ms is represented by water protons diffusing in small channels, experiencing slow diffusion exchange. The third component with a relaxation time between 113 and 135 ms (T2 3 ) is constituted by the superimposition of signals originated by water protons in medium sized channels and the protons of the liquid fat phase [17]. The last population is made of water protons in channels with a dimension bigger than the threshold of slow diffusion exchange, with relaxation time (T2 4 ) influenced by the presence of whey proteins and saccharides in solution (serum).…”
Section: T2 Relaxationmentioning
confidence: 99%
“…This phenomenon poses an issue in assigning a single system component to each exponential function. As a matter of fact, the distribution of liquid fat and of slow diffusive water molecules overlaps in mozzarella cheese [17].…”
Section: T2 Relaxationmentioning
confidence: 99%